ANTIDIABETIC EFFECT OF POTERIUM SPINOSUM LINN. IN ALLOXAN DIABETIC RATS - Waheed, Abdul; Baig, Javed Altaf; Rahman, M. Ataur (Journal of Ayub Medical College Abbottabad, 1989)
Hypoglycemic activity in many plant extracts is known to exist but the possible mechanism of action has not been worked out in most of the cases. The water extract of roots of Poterium spinosum has been known for its hypoglycemic activity in Arab countries. It is a bush like plant which grows abundantly and is called nBullan" in Arabic language. The roots are washed and boiled in water which gives a brick red colour extract. Hypoglycemic activity vim studied in normal and alloxan diabetic rats. The activity was compared with phenformin. The liver was rapidly removed and clamped in liquid nitrogen to determine the metabolites. A significant hypoglycemic effect in alloxan diabetic rats was observed and about 60% decrease in blood glucose level was found after 3 hours of administration of the extract. The extract was not found to be effective in normal rats. There was a simultaneous reduction in blood and liver glucose, in blood triglycerides level. While blood and liver lactate concentration increased significantly. The hypoglycemic activity of extract was compared with Phenformin and was found to be more potent. The extract of Poterium spinosum has a significant hypoglycemic activity which could be useful for oral treatment of Diabetes mellitus. Key Words: Hypoglycemic, Poterium spinosum, alloxan, rats.